Digitalization of Russian industry: the state and prospects of development in the conditions of sanctions and restrictions - S. G. Vagin (Вестник университета)
The article presents an assessment of the main statistical indicators related to the efficiency of industrial production growth in various regions of Russia over the past few years. The inclusion of digital achievements in the context of the negative consequences of the recent pandemic and sanctions on the production of industrial enterprises is also considered. The research is devoted to the application of digital technologies in industrial production in Russia in several regions under current circumstances and the potential of their future development. The introduction contains an overview of the scientific literature of economists and researchers dealing with industrial production and digitalization. This section also outlines the goals and objectives of the study. The purpose of the study is to study the current state of industrial production growth in Russian regions, depending on the development of the regional economy under sanctions. The assessment of industrial growth indicators of the main economic indicators of industrial enterprises is carried out. There was also a study of methods and researchers who contributed to the consideration of this issue both at the national and international level. The article considered indicators illustrating the growth of Russian industrial production and its regional variations, as well as evaluating the use of digital technologies in industrial production. At the conclusion of the article, based on the scientific work carried out and a review of the literature of researchers who studied this issue, the result was summed up. The essence of this conclusion suggests that the reorganization of industrial production at the level of regional management should continue in the foreseeable future. Additionally, a long-term forecast for the development of industrial production has been compiled.